PENGEMBANGAN MEDIA KOMIK DIGITAL UNTUK PERILAKU MORAL DAN AGAMA BAGI ANAK USIA 5-6 TAHUN DI TK AL-HUSNA PEKANBARU - Santi Tarigan; Zulkifli N Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the development of digital comic media from media design to the formation of moral and religious behavior of children aged 5-6 years at TK Al Husna Pekanbaru. The type of research used is R&D which is to develop products used in education and learning. This study uses data collection techniques through observation and interviews. Data analysis is quantitative descriptive. The subjects of this study were 5 children, because it used a limited trial. The results of the study indicate that the development of digital comic media for the formation of moral and religious behavior in early childhood is appropriate to be used as an educative learning medium.Keywords: Digital Comic Media, Moral And Religious Behavior, Early Childhood